Cheap Qurban Syariah Investment (CQSI) Program, Empowerment and Price Stabilization - Ardi Novra; Adriani Adriani; Depison Depison; Ade Octavia (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2020)
The research objective to develop a model of ummah fund utilization in the form of Cheap Qurban Syariah Investment (CQSI) with the synergy between the purpose of worship and the value of social benefits for the ummah empowerment. The study method used in the model design analyzes the beef cattle market's behavior, and a cost-benefit analysis of sharia investment in the pattern of profit sharing, the added value of beef cattle fattening efforts. Using the cost-benefit analysis of the profit-sharing partnership scheme, it was found that investment in cheap Qurban programs reduced the cost of Qurban borne by participants by 19.79% without lowering the Share of income received by beef cattle breeder partners and management fees for managing institutions. The more extended flexibility of procurement of feeder cattle when the conditions of low market demand and the reduced pressure on demand for ready-to-cut cattle at the time of Qurban worship will indirectly reduce the excessive fluctuations in commodity market prices. Based on the model developed, it can be concluded that cheap Qurban programs can encourage the utilization of the potential of ummah funds for farmers' economic empowerment, business opportunities for entrepreneurs, and Islamic institutions and indirectly help stabilize commodity prices for beef cattle without reducing the actual value of worship.